Actions for the greening of power engineering to improve energy efficiency - Tadeusz Fijał (Economic and Environmental Studies (E&ES), 2018)
The greening of power engineering is a component of the ecologically sustainable development strategy being implemented in the world and also a pillar of the EU sustainable energy policy. One of the main fields of activity for the greening of power engineering are actions for improving power generating and use efficiency. Such actions are implemented to improve energy conversion efficiency in power generating processes or to reduce power consumption by end-users. The effect of these actions being carried out at an international level is to reduce fossil fuel consumption, provide energy security of states as well as preventing climate change by reducing greenhouse gas emissions. The aim of this paper is to present main directions of actions for the greening of power engineering related to energy efficiency improvement, and functional principles of the basic systems supporting these activities in Poland.
Keywords: Q49; Q58; 330; greening of power engineering; energy efficiency; white certificates